2008
DOI: 10.1021/tx800093k
|View full text |Cite
|
Sign up to set email alerts
|

Protein Targets of Reactive Metabolites of Thiobenzamide in Rat Liver in Vivo

Abstract: Thiobenzamide (TB) is a potent hepatotoxin in rats, causing dose-dependent hyperbilirubinemia, steatosis, and centrolobular necrosis. These effects arise subsequent to and appear to result from the covalent binding of the iminosulfinic acid metabolite of TB to cellular proteins and phosphatidylethanolamine lipids [ Ji et al. ( 2007) Chem. Res. Toxicol. 20, 701- 708 ]. To better understand the relationship between the protein covalent binding and the toxicity of TB, we investigated the chemistry of the adductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 76 publications
6
96
0
Order By: Relevance
“…40 Sulfonic and sulfenic acids are reactive electrophilic species which are capable of interacting with several intracellular targets such as different proteins. 41,42 In the current study, we found that NMT administration significantly damaged liver mitochondria both in vitro and in vivo. NMT reactive metabolites might also be involved in the mitochondrial injury induced by this chemical in vivo (Figure 7).…”
Section: Discussionsupporting
confidence: 53%
“…40 Sulfonic and sulfenic acids are reactive electrophilic species which are capable of interacting with several intracellular targets such as different proteins. 41,42 In the current study, we found that NMT administration significantly damaged liver mitochondria both in vitro and in vivo. NMT reactive metabolites might also be involved in the mitochondrial injury induced by this chemical in vivo (Figure 7).…”
Section: Discussionsupporting
confidence: 53%
“…A number of simple chemical compounds such as acetaminophen, bromobenzene, furosemide, methapyrilene (Graham et al 2008), and thiobenzamide (Ikehata et al 2008) produce hepatotoxicity, with damage to extrahepatic tissues in certain cases (bromobenzene is also pneumotoxic and nephrotoxic; Dahl et al 1990), in one or more rodent species after a single dose or a short-term regimen. The reproducibility of these injuries permits detailed mechanistic investigations that are impractical or unachievable in the case of idiosyncratic reactions; however, they may provide a source of crucial insights into the mechanisms of such reactions.…”
Section: Model Hepatotoxins: Role Of Reactive Metabolite Formationmentioning
confidence: 99%
“…Nevertheless, the structure of the metabolite-protein adduct has been determined in only a few cases (Baer et al 2007;Bambal and Hanzlik 1995;Damsten et al 2007;Sleno et al 2007;Yukinaga et al 2007;Zhang et al 2003), and identification of the modified amino acid residue in vivo remains a major analytical challenge (Koen et al 2006). Greater progress has been made in identification of the cellular proteins that are modified in vivo (Druckova et al 2007;Ikehata et al 2008;Koen et al 2007;Qiu et al 1998;Shipkova et al 2004). Potential targets within individual organelles can now be identified by using model electrophiles in cell fractions (Shin et al 2007;Wong and Liebler 2008).…”
Section: Model Hepatotoxins: Role Of Reactive Metabolite Formationmentioning
confidence: 99%
“…Antibody-based approaches to adduct detection have revealed a handful of targets for several chemicals, but only in a few cases has adduction been clearly defined at the level of amino acid sequence (Stewart et al, 2007;Ikehata et al, 2008). Thus, identifying specific sites of reactive chemical/metabolite-mediated modification within proteins has been extremely challenging.…”
Section: Introductionmentioning
confidence: 99%